Inventarisasi Kupu-Kupu (Lepidoptera: Rhopalocera) di Suaka Margasatwa Paliyan, Gunung Kidul - uliya fasa (Berkala Ilmiah Biologi, 2023)
A wildlife sanctuary is a location where the environment is still preserved so as to minimize forest conversion activities. Roaming method or exploration is the method that the autor uses in research butterfly inventory. Exploration is carried out by following the transect which adjusts the shape of the location with a distance between points of 20 meters. Areas that become observation locations including open land, fields, forest medium mixed and dense mixed forest. Butterfy data obtained through documentation or captured using insect nets observed, then release again. The aim of this research is identify butterfly species and environmental parameters present in the field clearing, field, medium ixed forest, and dense mixed forest. Results of the study are found 22 species butterflies with a total of 65 indiviuals. Previously, research related to butterfly inventory in Wildlife Sanctuary Paliyan has never been done. The conservation of butterflies is need because of the importance of the presence of butterflies as a determinant of environmental quality. Butterfly diversity disclosure can be used as a related database types of butterflies in Indonesia, especially the Paliyan Wildlife Sanctuary.